Dietary patterns and colorectal cancer risk in a Korean population: A case-control study. Issue 25 (June 2016) - Park, Yoon; Lee, Jeonghee; Oh, Jae Hwan; Shin, Aesun; Kim, Jeongseon
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Colorectal cancer (CRC) has been recognized as one of the major malignancies in Korea. Analyses of dietary patterns can provide insight into the complex interactions of foods, nutrients, and biologically active components within a diet, which vary among populations. We aimed to investigate the associations between dietary patterns and colorectal cancer risk in Koreans. In a study of 923 cases and 1846 controls, principal component analysis was used to identify dietary patterns based on 33 predefined food groups using a 106-item semiquantitative food frequency questionnaire (SQFFQ). The associations between dietary patterns and CRC risk were assessed using binary and polytomous logistic regression models to estimate odds ratios (ORs) and 95% confidence intervals (CIs). Three dietary patterns (traditional, Westernized, and prudent) were derived. The proportion of total variation explained by 3 patterns was 24.2% for men and 25.3% for women. The traditional and prudent patterns were inversely associated with CRC risk [OR and 95% CI for the highest intake tertile of pattern score vs. the lowest = 0.35 (0.27–0.46) and 0.37 (0.28–0.48), respectively], whereas the Westernized pattern showed a positive association, especially among women [OR = 2.13 (1.35–3.34) for the highest tertile vs. the lowest]. A decrease in CRC risk among those with the highest intake of the prudent pattern was observed in all anatomical subsites in both men [OR = 0.36 (0.19–0.68) for proximal colon; 0.21 (0.12–0.36) for distal colon; 0.28 (0.18–0.44) for rectum] and women [OR = 0.28 (0.11–0.71); 0.27 (0.13–0.54); 0.45 (0.25–0.83)]. Our results indicate that individuals who prefer the Westernized dietary pattern should be made aware of their increased CRC risk. The traditional dietary pattern and the prudent pattern, which are rich in fruits and dairy products, are recommended for the Korean population to prevent CRC.